2019
DOI: 10.3390/pr7080486
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Analytical Investigation of an Unsteady Thin Film Nanofluid Flow over an Angular Surface

Abstract: In the present study, we examine three-dimensional thin film flow over an angular rotating disk plane in the presence of nanoparticles. The governing basic equations are transformed into ordinary differential equations by using similarity variables. The series solution has been obtained by the homotopy asymptotic method (HAM) for axial velocity, radial velocity, darning flow, induced flow, and temperature and concentration profiles. For the sake of accuracy, the results are also clarified numerically with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For example, Rehman and Nadeem [34] investigated heat convective analysis for multi-directional stagnation flow movement. Khan (along with other researchers) [35][36][37][38][39][40] has studied the effects of thermal convection and MHD fluid flow. In studying the above articles, it has been found that wire coating techniques with MHD of a viscoelastic Eyring-Powell liquid as the coating substance has not yet been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rehman and Nadeem [34] investigated heat convective analysis for multi-directional stagnation flow movement. Khan (along with other researchers) [35][36][37][38][39][40] has studied the effects of thermal convection and MHD fluid flow. In studying the above articles, it has been found that wire coating techniques with MHD of a viscoelastic Eyring-Powell liquid as the coating substance has not yet been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Aliakbar et al [23] discussed the effects of thermal radiation over a stretch surface on the MHD flow of Maxwellian fluids. Rasheed et al [24,25] investigated heat transfer analysis in two-dimensional viscoelastic incompressible fluid with nonuniform heat generation over a permeable stretching sheet in the presence of uniform magnetic field. To solve the higher-order differential equation, the Liao's homotopy analysis method [26,27] is very useful.…”
Section: Introductionmentioning
confidence: 99%
“…Hsiao [10] has worked on an incompressible uniform MHD stagnation point movement of a second-order viscoelastic liquid and thermal conduction caused by a flow oscillating surface, and it is observed that viscoelastic liquid flow thermal effect is better than nonviscoelastic liquid flow thermal effect. Rasheed et al [11] analyzed numerical and analytical investigation of thin-film nanofluid flow over an angular surface. Roşca et al [12] presented an analysis for the uniform boundary-layer movement and heat transformation of a non-Newtonian fluid in the stagnation point along with unsteady propagating plane sheet of the unrestricted flow slip velocity and presented a dual (upper and lower branch) solution for certain variables.…”
Section: Introductionmentioning
confidence: 99%